Dynamic batch rekeying scheme using multiple logical key trees for secure multicast communication - Senan, Shayma; Hassan Abdalla Hashim, Aisha; Othman, Raihan; Az Eddine, Azeddin; Zeki, Akram M. (2015)
A group key management has an important role in multicast security in order to achieve data integrity and confidentiality. Key trees are ideal for a group of users to efficiently and securely share a common secret key, the group key, which can encrypt transmitted data, or other session keys that protect group communication. A new group key management protocol is proposed for centralized dynamic groups. A one-way key derivation are integrated with multiple logical key trees to reduce the communication overhead of rekeying operations. The server does not have to send new keys to those members who can derive the keys by themselves, and the total number of encrypted keys transmitted per rekeying operation becomes fewer. The performance analysis of the proposed scheme shows that it has less communication cost than the other compared protocols.